The Influence of Leadership and Work Environment on Teachers’ Work Discipline in Schools SMK Putra Anda Binjai - Annisa Febrianti; Wilchan Robain; Emi Wakhyuni (Cattleya Darmaya Fortuna, 2026)
This study aims to determine the extent to which leadership and the work environment influence teachers’ work discipline at SMK Putra Anda Binjai, both partially and simultaneously. The sample used in this study consisted of 70 teachers working at SMK Putra Anda Binjai. The research method employed was a quantitative approach using a Likert scale questionnaire for data collection. Hypothesis testing was conducted using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS version 26. The results indicate that leadership and the work environment influence teacher work discipline at SMK Putra Anda Binjai, with the following findings: (1) Leadership has a positive effect on work discipline, with a calculated t-value greater than the critical t-value (3.217 > 1.996) and a significance level of 0.002. (2) The work environment has a positive effect on work discipline, with a calculated t-value greater than the critical t-value (2.173 > 1.996) and a significance level of 0.000. (3) Leadership and the work environment have a significant effect on teachers’ work discipline at SMK Putra Anda Binjai, with a calculated F-value greater than the critical F-value (59.033 > 3.134) and a significance level of 0.000. (4) Leadership and the work environment together have a positive and significant effect on work discipline, with an R-Square value of 0.638. These results indicate a simultaneous effect of the leadership and work environment variables on work discipline, as evidenced by the equation for the unstandardized coefficient B: Y = (5.965) + 0.384X1 + 0.430X2 + e.